Properties of AOT reverse micelle interfaces with different polar solvents1. (25th January 2016) - Luna, M. Alejandra; Correa, N. Mariano; Silber, Juana J.; Falcone, R. Dario; Moyano, Fernando
Abstract : The behavior of polar solvents such as formamide, ethylene glycol, propylene glycol, glycerol, dimethylformamide (DMF), and dimethylacetamide (DMA), entrapped in n ‐heptane/sodium 1, 4‐bis‐2‐ethylhexylsulfosuccinate (AOT ) reverse micelles (RMs) was investigated using absorption, emission, and the red edge excitation shift technique. We use the solvatochromism behavior of the hemycianine 4‐(4‐[dimethylamino]‐styryl)‐1‐methylpyridinium iodide (HC) to investigate the physicochemical properties such as micropolarity, microviscosity, and hydrogen bond (H‐bond) interaction in the non‐aqueous RMs. Our results demonstrate thatAOT surfactant interacts through H‐bond with formamide, ethylene glycol, propylene glycol, and glycerol, and this interaction is responsible for weakening the electrostatic interaction between HC‐AOT when entrapped in n ‐heptane/AOT RMs in absence of a polar solvent. On the other hand, when non‐H‐bond donor solvents (DMF and DMA) are incorporated inside the RMs, the structure of both pure solvents is destroyed upon encapsulation by the Na + ‐DMF or Na + ‐DMA interaction at Ws (Ws = [polar organic solvent]/[AOT]) ≤1.5. Our results show how the physicochemical properties, such as micropolarity, microviscosity, and H‐bond interaction, of non‐aqueous n ‐heptane/AOT RMs interfaces can be dramatically changed by simply using different non‐aqueous polar solvent. Thus, these results can be very useful for employing these RMs, stabilizing enzymes, and using them as nanoreactors. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Sensing different interfacial properties of n ‐heptane/AOT non‐aqueous using HC as molecular probe.